Stability analysis of nonholonomic multiagent coordinate‐free formation control subject to communication delays - González, Antonio; Aragüés, Rosario; López‐Nicolás, Gonzalo; Sagüés, Carlos (International journal of robust and nonlinear control, 2018)
Summary This paper investigates the convergence of nonholonomic multiagent coordinate‐free formation control to a prescribed target formation subject to communication delays by means of Lyapunov‐Krasovskii approach and smooth state‐feedback control laws. As a result, an iterative algorithm based on linear matrix inequalities is provided to obtain the worst‐case point‐to‐point delay under which the multiagent system is guaranteed to be stable. It is worth mentioning that: (i) the given algorithm holds for any connected communication topology and (ii) the formation control is coordinate‐free, that is, a common frame is not required to be shared between agents. The effectiveness of the given method is illustrated through simulation results.